2016
DOI: 10.1002/er.3532
|View full text |Cite
|
Sign up to set email alerts
|

A novel choice for the photovoltaic-thermoelectric hybrid system: the perovskite solar cell

Abstract: SUMMARYMost of the recent studies about the photovoltaic cell-thermoelectric generator (PV-TEG) hybrid system pay their attention to silicon PV cells. This paper is to estimate the feasibility and features of the integrated system consisting of the emerging perovskite solar cells and thermoelectric modules. The results in this paper show that the temperature coefficient of the perovskite solar cell is lower than 2‰. Because of such a lower temperature coefficient, the efficiency of the perovskite solar cell-TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 29 publications
(38 reference statements)
0
27
0
1
Order By: Relevance
“…The concentration ratio is a function of the configuration of the solar concentrator used for the hybrid system. The kind of configuration determines the intensity of energy reaching the PV converter and consequently on the performance and the cost of the system . Beeri et al illustrated experimentally and numerically using an integrated hybrid system with a multijunction solar cell and a TEG that maximum efficiency of 32% could be reached with a concentrated factor X ≤ 200.…”
Section: Hybrid Pv‐tegmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration ratio is a function of the configuration of the solar concentrator used for the hybrid system. The kind of configuration determines the intensity of energy reaching the PV converter and consequently on the performance and the cost of the system . Beeri et al illustrated experimentally and numerically using an integrated hybrid system with a multijunction solar cell and a TEG that maximum efficiency of 32% could be reached with a concentrated factor X ≤ 200.…”
Section: Hybrid Pv‐tegmentioning
confidence: 99%
“…The kind of configuration determines the intensity of energy reaching the PV converter and consequently on the performance and the cost of the system. 76 Beeri et al 65 illustrated experimentally and numerically using an integrated hybrid system with a multijunction solar cell and a TEG that maximum efficiency of 32% could be reached with a concentrated factor X ≤ 200. At this concentrating factor, the major contributor to the overall efficiency comes from the PV.…”
Section: Concentration Ratiomentioning
confidence: 99%
“…Perovskites have been widely studied as functional materials in the fields of photovoltaic applications, fuel cells, solar cells, hydrogen storage, as well as being catalysts for oxidation . 7‐13 …”
Section: Introductionmentioning
confidence: 99%
“…Perovskite quantum dots (QDs) and traditional QDs in the light‐emitting diode, solar cells, sensors, and other fields have made rapid development . Kovalenko et al reported that CsPbX 3 (X = Cl, Br, and I) QDs exhibit high photoluminescence (PL) efficiency (~90%) and narrow full width at half maximum (FWHM), which is superior to that of most traditional QDs.…”
Section: Introductionmentioning
confidence: 99%